Geomorphological control on boulder transport and coastal erosion before, during and after an extreme extra‐tropical cyclone. Issue 5 (25th February 2016) - Naylor, Larissa A.; Stephenson, Wayne J.; Smith, Helen C. M.; Way, Oliver; Mendelssohn, James; Cowley, Andrew
Abstract: Extreme wave events in coastal zones are principal drivers of geomorphic change. Evidence of boulder entrainment and erosional impact during storms is increasing. However, there is currently poor time coupling between pre‐ and post‐storm measurements of coastal boulder deposits. Importantly there are no data reporting shore platform erosion, boulder entrainment and/or boulder transport during storm events – rock coast dynamics during storm events are currently unexplored. Here, we use high‐resolution (daily) field data to measure and characterize coastal boulder transport before, during and after the extreme Northeast Atlantic extra‐tropical cyclone Johanna in March 2008. Forty‐eight limestone fine‐medium boulders ( n = 46) and coarse cobbles ( n = 2) were tracked daily over a 0.1 km 2 intertidal area during this multi‐day storm. Boulders were repeatedly entrained, transported and deposited, and in some cases broken down ( n = 1) or quarried ( n = 3), during the most intense days of the storm. Eighty‐one percent ( n = 39) of boulders were located at both the start and end of the storm. Of these, 92% were entrained where entrainment patterns were closely aligned to wave parameters. These data firmly demonstrate rock coasts are dynamic and vulnerable under storm conditions. No statistically significant relationship was found between boulder size (mass) and net transport distance. Graphical analyses suggest that boulder size limits the maximum longshore transport distance but that for the majority of boulders lying under this threshold, other factors influence transport distance. Paired analysis of 20 similar sized and shaped boulders in different morphogenic zones demonstrates that geomorphological control affects entrainment and transport distance – where net transport distances were up to 39 times less where geomorphological control was greatest. These results have important implications for understanding and for accurately measuring and modelling boulder entrainment and transport. Coastal managers require these data for assessing erosion risk. © 2016 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd.